2015
DOI: 10.5194/acp-15-6651-2015
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian analysis of microphysical and chemical processes in the Antarctic stratosphere: a case study

Abstract: Abstract. We investigated chemical and microphysical processes in the late winter in the Antarctic lower stratosphere, after the first chlorine activation and initial ozone depletion. We focused on a time interval when both further chlorine activation and ozone loss, but also chlorine deactivation, occur.We performed a comprehensive Lagrangian analysis to simulate the evolution of an air mass along a 10-day trajectory, coupling a detailed microphysical box model to a chemistry model. Model results have been co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Some studies focused on the validation of convective waves (Kim et al, 2009;Grimsdell et al, 2010;Stephan and Alexander, 2015;Wu et al, 2015), but case studies for mountain waves have also been conducted (Orr et al, 2015). The validation of explicitly resolved temperature fluctuations in high-resolution meteorological analyses is of particular interest to Lagrangian studies that could potentially use these data to study PSC formation Hoyle et al, 2013;Grooß et al, 2014;Di Liberto et al, 2015). We used the AIRS data to evaluate explicitly resolved temperature fluctuations due to gravity waves in the European Centre for Medium-Range Weather Forecasts (ECMWF) operational analysis for a set of 21 large-amplitude gravity wave events in the polar winter seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies focused on the validation of convective waves (Kim et al, 2009;Grimsdell et al, 2010;Stephan and Alexander, 2015;Wu et al, 2015), but case studies for mountain waves have also been conducted (Orr et al, 2015). The validation of explicitly resolved temperature fluctuations in high-resolution meteorological analyses is of particular interest to Lagrangian studies that could potentially use these data to study PSC formation Hoyle et al, 2013;Grooß et al, 2014;Di Liberto et al, 2015). We used the AIRS data to evaluate explicitly resolved temperature fluctuations due to gravity waves in the European Centre for Medium-Range Weather Forecasts (ECMWF) operational analysis for a set of 21 large-amplitude gravity wave events in the polar winter seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The question of the shape of NAT particles is in fact far from being clarified and has important implications for the denitrification mechanisms of the polar stratosphere, an important step in the process that leads to the destruction of stratospheric ozone. In fact, the sedimentation of large NAT particles is considered one of the main causes of denitrification of the polar winter stratosphere (Di Liberto et al, 2015). Their settling time influences this process, and it is in turn dependent on the NAT particles' shape and size, both of which determine their settling speed and lifetime and hence their denitrification efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we are interested in gravity waves because they can provide significant local temperature fluctuations that can trigger the formation of PSCs, even if synoptic-scale temperatures are above formation thresholds. Case studies of mountain waves induced by the Scandinavian Mountains showed that the waves can cause localized cooling of up to 10-15 K (Carslaw et al, 1998b;Dörnbrack et al, 1999Dörnbrack et al, , 2002. The Antarctic Peninsula is another well-known hot spot for the formation of PSCs from mountain waves in the Southern Hemisphere (Wu and Jiang, 2002;Shibata et al, 2003;Höpfner et al, 2006b;Baumgaertner and McDonald, 2007;Eckermann et al, 2009;Orr et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies focused on the validation of convective waves (Kim et al, 2009;Grimsdell et al, 2010;Stephan and Alexander, 2015;Wu et al, 2015), but case studies for mountain waves have also been conducted (Orr et al, 2015). The validation of explicitly resolved temperature fluctuations in high-resolution meteorological analyses is of particular interest to Lagrangian studies that could potentially use these data to study PSC formation (Engel et al, 2013;Hoyle et al, 2013;Grooß et al, 2014;Di Liberto et al, 2015). We used the AIRS data to evaluate explicitly resolved temperature fluctuations due to gravity waves in the European Centre for Medium-Range Weather Forecasts (ECMWF) operational analysis for a set of 21 large-amplitude gravity wave events in the polar winter seasons.…”
Section: Introductionmentioning
confidence: 99%